2021
DOI: 10.1021/acs.jpcb.0c10318
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Kinetic Isotope Effects in R67 Dihydrofolate Reductase from Path-Integral Simulations

Abstract: Calculation of temperature-dependent kinetic isotope effects (KIE) in enzymes presents a significant theoretical challenge. Additionally, it is not trivial to identify enzymes with available experimental accurate intrinsic KIEs in a range of temperatures. In the current work, we present a theoretical study of KIEs in the primitive R67 dihydrofolate reductase (DHFR) enzyme and compare with experimental work. The advantage of R67 DHFR is its significantly lower kinetic complexity compared to more evolved DHFR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 152 publications
0
8
0
Order By: Relevance
“…Note that KIEs calculated with both the gasphase and full enzyme conditions, using other tunneling models and other computation methods, were sometimes also found to be underestimated compared to the experimental ones for the hydride transfer reactions in dihydrofolate dehydrogenases from different sources. 53,54 Therefore, assigning a specific DAD TRS to each system by directly matching the calculated with observed 2°KIEs does not appear to be possible. However, a comparison of the observed 2°KIEs of the three reactions with those calculated as a function of both substituent and DAD TRS could possibly differentiate the DAD TRS 's that the reactions use.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Note that KIEs calculated with both the gasphase and full enzyme conditions, using other tunneling models and other computation methods, were sometimes also found to be underestimated compared to the experimental ones for the hydride transfer reactions in dihydrofolate dehydrogenases from different sources. 53,54 Therefore, assigning a specific DAD TRS to each system by directly matching the calculated with observed 2°KIEs does not appear to be possible. However, a comparison of the observed 2°KIEs of the three reactions with those calculated as a function of both substituent and DAD TRS could possibly differentiate the DAD TRS 's that the reactions use.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The latter primitive enzyme has a simpler (thinner) and looser protein structure, which results in a loose active site and even allows the environmental water to leak through, making the KIE more T-dependent. 84,85 In our reaction, when the localized inner acetonitrile solvation shell around the TRS becomes thin enough to allow the chloroform to leak through, the CT complexation in the TRS becomes loose, and the KIE also becomes more T-dependent (insets A to D in Figure 4). The results from enzymes have been explained in terms of the destruction of the enzyme active site structure and thus the naturally evolved active site thermal vibrations so that the efficient short DAD TRS sampling becomes difficult, causing stronger T-dependence of KIEs.…”
Section: The Journal Ofmentioning
confidence: 99%
“…Kinetic studies of mutant methylenetetrahydrofolate dehydrogenase/cyclohydrolase activities of MTHFD1 have indicated that the change of kinetic isotope ratio in the dehydrogenase activity, and that Tyr52 (corresponding to Tyr84 in MTHFD2) plays a role in binding and orientation of the substrate. Furthermore, Lys56 (corresponds to Lys88 in MTHFD2) was proposed to possess a catalytic role [ 49 , 50 ]. However, after analyzing the data (Table 4 in Ref.…”
Section: Discussionmentioning
confidence: 99%